Effects of Pervari Honey from Türkiye on Proliferation, Oxidative Stress, and Apoptosis of Human Breast Cancer Cells - Ramazan Üzen; Hamiyet Altuntaş; Mustafa Çakır; Pınar Altın Çelik; Muazzez Derya Andeden (Journal of Advanced Research in Natural and Applied Sciences)
Breast cancer is one of the most common causes of deaths worldwide. Major obstacles to treatment have contributed to the increasing popularity of complementary or alternative therapies. Although recent results support the mechanism that honey induces cell death, the full mechanisms are still unknown. This study investigates the potential use of Pervari honey (PH) as an in vitro therapeutic agent in breast cancer. Firstly, the antioxidant capacity and total phenolic content of PH were tested. In addition, MCF-7 and MDA-MB-231 breast cancer cells treated with PH were examined for cell viability, reactive oxygen species production, oxidative deoxyribonucleic acid (DNA) damage, and apoptosis. Our results show that PH treatment decreased cell viability dose-dependently and increased reactive oxygen species (ROS) levels, oxidative DNA damage, and apoptosis rate. The present study suggests that honey is a promising source to produce pharmaceuticals and nutraceuticals for breast cancer therapy.